Compensation of large motion sensor displacements during long recordings of limb movements - Karch, Dominik; Kim, Keun-Sun; Wochner, Katarzyna; Philippi, Heike; Pietz, Joachim; Dickhaus, Hartmut (Journal of biomechanics, 2010)
In motion capture applications using electromagnetic tracking systems the process of anatomical calibration associates the technical frames of sensors attached to the skin with the human anatomy. Joint centers and axes are determined relative to these frames. A change of orientation of the sensor relative to the skin renders this calibration faulty. This sensitivity regarding sensor displacement can turn out to be a serious problem with movement recordings of several minutes duration. We propose the “dislocation distance” as a novel method to quantify sensor displacement and to detect gradual and sudden changes of sensor orientation. Furthermore a method to define a so called fixed technical frame is proposed as a robust reference frame which can adapt to a new sensor orientation on the skin. The proposed methods are applied to quantify the effects of sensor displacement of 120 upper and lower limb movement recordings of newborns revealing the need for a method to compensate for sensor displacement. The reliability of the fixed technical frame is quantified and it is shown that trend and dispersion of the dislocation distance can be significantly reduced. A working example illustrates the consequences of sensor displacement on derived angle time series and how they are avoided using the fixed technical frame.
Gesehen am 02.03.2023